(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
To improve the quality of life of patients with dilated veins, suspected varicose veins and patients with comorbidities who do not have indications for a high level of invasiveness, to study the degree of change in working capacity and provide information about it.